A Qualitative and quantitative approach about a ludic strategy for teaching-learning: The triominoes of genetics - Clarindo , Wellington; Ferreira da Conceição, Suelen; Weiss, Andreia; de Souza Marçal, Tiago; Ferreira, Adésio (Guará Journal, 2022)
Learning is a systematic and interactive process that involves the exchange of information between pupils and teachers. The knowledge constructed during the learning process represents the basis for the cognitive, emotional and psychomotor edu-cation of the student, further contributing to the teacher’s for-mation. Among the different subjects approached during basic education, and especially secondary school, Genetics is one that presents complex concepts, making it difficult for pupils to comprehend and therefore learn. With the aim of facilitating the process of teaching-learning the basic concepts of Genetics, the present study elaborated and applied a new ludic proposal, the game Triominoes. In this scope, Triominoes was created with 40 triangular tiles containing, on each face, complementary terms and concepts. Based on the answers to a questionnaire applied after the activity, this ludic strategy was analyzed qualitatively and quantitatively. Through these analyses, the Triominoes hel-ped in the teaching-learning process, the development of logi-cal-deductive reasoning, exploring the cognitive, emotional and psychomotor abilities of the learners. Therefore, Triominoes can be considered an innovative, viable and low-cost pedagogical material, which could be routinely employed for the teaching of Genetics as well as other contents from different subjects of the basic, secondary and higher education.